(untitled) (Eurasian Journal of Humanities and Social Sciences, 2024)
The rapid development of globalization has also accelerated the development of technogenic civilization processes. Enjoying the achievements of the developing technogenic civilization, assimilating the experiences of the countries of the world in its creation, and looking for all the opportunities and ways to join the ranks of developed countries are extremely important for the young sovereign countries that are now on the road to development. is an important requirement. At a time when countries, nations and peoples of the world are constantly searching for new, modern ways to meet today’s demands, it will do no good to simply watch from the sidelines. Therefore, it is necessary for every nation, people and country to live according to the demands of the times, to keep pace with people’s lives, to prepare conditions for the realization of their dreams and aspirations, and to use all opportunities effectively